Novel Borrelia Genotypes from Brazil Indicate a New Group of Borrelia spp. Associated with South American Bats. Issue 1 (21st October 2022) - Jorge, Felipe R; Muñoz-Leal, Sebastián; de Oliveira, Glauber M B; Serpa, Maria Carolina A; Magalhães, Meylling M L; de Oliveira, Lorena M B; Moura, Francisco B P; Teixeira, Bruno M; Labruna, Marcelo B
Abstract: The bacterial genus Borrelia comprises vector-borne spirochetes that have been classified into three major groups: the relapsing fever group (RFG), the Borrelia burgdorferi Johnson, Schmid, Hyde, Steigerwalt & Brenner sensu lato group (Bbsl), and the reptile-monotreme group (RMG). All three groups have been associated mainly with ticks and wild animals, especially rodents, birds, and reptiles. Here, we searched for Borrelia infection among 99 vampire bats [ Desmodus rotundus (É. Geoffroy)] (Chiroptera: Phyllostomidae) from the Brazilian semiarid region. Through molecular investigation of bat internal organs, haplotypes of a potentially novel Borrelia organism were detected in 5% (5/99) of the bats. Borrelia DNA was detected in the liver, blood, spleen, kidney and brain, suggesting a systemic infection. Phylogenetic analyses inferred from partial sequences of the borrelial rrs and flaB genes indicated that the vampire bat-associated Borrelia sp. of this study form a monophyletic group with a newly reported Borrelia associated with a Colombia bat, distinct from the three main currently recognized groups of Borrelia spp., Bbsl, RFG, and RMG. These novel bat-associated Borrelia spp. from South America might have arisen through an independent event along the borrelial evolutionary history, since previous molecular reports of Borrelia organisms in bats or bat-associated ticks from Africa, Europe, and North America were all classified in the RFG.